Data and computer communications - Stallings, William (Prentice Hall, 2011)
Contents: Data and Computer Communications, 9e, is a two-time winner of the best Computer Science and Engineering textbook of the year award from the Textbook and Academic Authors Association. It is ideal for one/two-semester courses in Computer Networks, Data Communications, and Communications Networks in CS, CIS, and Electrical Engineering departments.